Evaluación de producción y rentabilidad del proyecto porcicola de la asociación del recinto cuatro mangas, Buena fe. - Meza Bravo, Yanela Dalila. (2016)
Four Campus Association Mangas work four years ago, with a porcicola project, funded by the Autonomous Government Decentralized Prefecture of the province of Los Rios (PDAG). This research diagnosed porcicola production and profitability of the association of the enclosure four sets of Canton Good Faith. Having used the inductive and deductive method and tools such as surveys and interviews, establishing the Association has not had access to credit and the production activities made with own resources and with the help of programs producticos Prefecture of the province. The lead management system associated the use of pigs confined within the piggeries, recorded in a field notebook, available for breeding animals, data supply, sales, health problems and immunization records, inspecting animals one hour daily basis. The type of construction of the pig is mixed, built in an area of 60 m2, divided into two cubicles. Given the genetic makeup and Durocjercey Pientrain equally, feeding pigs with more balanced food home, that once pigs reach more than 100 kg, they are marketed, some fishing and other animals standing. Showing that about half of its sales make the difference dressing and walking, and at the time of our investigation prices fluctuated between 1.80 and $ 2.11, depending on the time and manner of sale. In the absence of an internal structural organization that contributes to have first-hand that the reality of their production operations is known, a proposal for the improvement and continuity of pig production and administration were executed on the basis of the results obtained may contribute in making administrative and productive decisions for members, meaning an improvement in the economic aspect and hence the social aspect, by providing more resources to meet their needs and family operations.